1997
DOI: 10.1161/01.cir.95.10.2387
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytokine Expression in Leukocytes by Binding of Thrombin-Stimulated Platelets

Abstract: In patients with AMI, leukocyte-platelet adhesion is increased. Binding of activated platelets induces IL-1 beta, IL-8, and MCP-1 in leukocytes. Our findings suggest that leukocyte-platelet adhesion contributes to the regulation of inflammatory responses in AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
222
0
10

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(242 citation statements)
references
References 43 publications
10
222
0
10
Order By: Relevance
“…A functional soluble form of CD40L has recently been reported (39,40), suggesting that platelets may stimulate MC through either soluble or cell-surface CD40L. In contrast to data obtained in other cell types (11,12), blockade of P-selectin on platelets did not decrease MCP-1 production in coculture. Although we used doses of the anti-P-selectin mAb that can be expected to almost completely block surfaceexpressed P-selectin, mesangial production of MCP-1 was not significantly decreased.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A functional soluble form of CD40L has recently been reported (39,40), suggesting that platelets may stimulate MC through either soluble or cell-surface CD40L. In contrast to data obtained in other cell types (11,12), blockade of P-selectin on platelets did not decrease MCP-1 production in coculture. Although we used doses of the anti-P-selectin mAb that can be expected to almost completely block surfaceexpressed P-selectin, mesangial production of MCP-1 was not significantly decreased.…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly in our previous study, which examined the interaction between monocytes and MC, both cell-to-cell contact and soluble factors were required for the maximum activation of the latter (18). Other studies have shown that platelet contact induces chemokine or adhesion molecule expression by endothelial cells or leukocytes through NF-B activation (10,12). NF-B plays a critical role in inflammatory response through induction of a variety of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar processes occur in patients with COPD (Ferroni et al, 2000), atherosclerosis (Arber et al, 1991;Ott et al, 1996;Neumann et al, 1997;Sarma et al, 2002;Huo et al, 2003) and RA (Joseph et al, 2001;Bunescu et al, 2004). In this regard, experimental models of disease have provided evidence for a requirement of platelets in pulmonary eosinophil and lymphocyte recruitment in rabbits, guineapigs and mice in models of allergic inflammation (LellouchTubiana et al, 1988;Coyle et al, 1990;Pitchford et al, 2003Pitchford et al, , 2005; and neutrophil and monocyte recruitment in atherosclerosis (Arber et al, 1991;Neumann et al, 1997;Hayward et al, 1999) and RA (Schmitt-Sody et al, 2005). This phenomenon requires intact platelets expressing mediators on the cell surface, and in common with the occurrence of leukocyte recruitment in inflammatory diseases, platelet Pselectin is of particular importance (Diacovo et al, 1996a, b;Schober et al, 2002;Huo et al, 2003;Pitchford et al, 2005).…”
Section: Leukocyte Recruitment and Activation: Influence Of Plateletsmentioning
confidence: 77%
“…For example, studies with un-separated leukocyte populations reveal a significant increase in platelet-leukocyte complexes in allergic mice and in human asthmatics (Pitchford et al, 2003(Pitchford et al, , 2005. Similar processes occur in patients with COPD (Ferroni et al, 2000), atherosclerosis (Arber et al, 1991;Ott et al, 1996;Neumann et al, 1997;Sarma et al, 2002;Huo et al, 2003) and RA (Joseph et al, 2001;Bunescu et al, 2004). In this regard, experimental models of disease have provided evidence for a requirement of platelets in pulmonary eosinophil and lymphocyte recruitment in rabbits, guineapigs and mice in models of allergic inflammation (LellouchTubiana et al, 1988;Coyle et al, 1990;Pitchford et al, 2003Pitchford et al, , 2005; and neutrophil and monocyte recruitment in atherosclerosis (Arber et al, 1991;Neumann et al, 1997;Hayward et al, 1999) and RA (Schmitt-Sody et al, 2005).…”
Section: Leukocyte Recruitment and Activation: Influence Of Plateletsmentioning
confidence: 96%